2016
DOI: 10.3389/fmicb.2016.01943
|View full text |Cite
|
Sign up to set email alerts
|

The Ecological Coherence of Temperature and Salinity Tolerance Interaction and Pigmentation in a Non-marine Vibrio Isolated from Salar de Atacama

Abstract: The occurrence of microorganisms from the Vibrio genus in saline lakes from northern Chile had been evidenced using Numerical Taxonomy decades before and, more recently, by phylogenetic analyses of environmental samples and isolates. Most of the knowledge about this genus came from marine isolates and showed temperature and salinity to be integral agents in shaping the niche of the Vibrio populations. The stress tolerance phenotypes of Vibrio sp. Teb5a1 isolated from Salar de Atacama was investigated. It was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 61 publications
0
17
0
Order By: Relevance
“…Moreover, cells grown in the absence of chloride were lacking flagella; however, it was restored upon the addition of chloride ( Roeßler et al, 2000 ). A recent report indicates that the salt concentration is dependent on motility in a pigment halotolerant Vibrio strain isolated from Salar de Atacama, but motility was inhibited in higher salt concentrations (150 g/l NaCl; Gallardo et al, 2016 ). Substantial energy is needed for flagellar biosynthesis and bacteria are able to inhibit certain processes in response to stress, motility was reduced, and biofilm formation was seen in SH31 ( Figure 4 ) a general bacterial response to osmotic stress found in diverse organisms, as it was shown in Pseudomonas putida ( Bojanovič et al, 2017 ).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Moreover, cells grown in the absence of chloride were lacking flagella; however, it was restored upon the addition of chloride ( Roeßler et al, 2000 ). A recent report indicates that the salt concentration is dependent on motility in a pigment halotolerant Vibrio strain isolated from Salar de Atacama, but motility was inhibited in higher salt concentrations (150 g/l NaCl; Gallardo et al, 2016 ). Substantial energy is needed for flagellar biosynthesis and bacteria are able to inhibit certain processes in response to stress, motility was reduced, and biofilm formation was seen in SH31 ( Figure 4 ) a general bacterial response to osmotic stress found in diverse organisms, as it was shown in Pseudomonas putida ( Bojanovič et al, 2017 ).…”
Section: Discussionmentioning
confidence: 98%
“…The effect of several stress factors were studied in an Enterobacter strain isolated from a high-altitude Andean saline lake ( Dib et al, 2008 ). One member of the Vibrio genus, Vibrio ruber , is one the most studied halophilic eubacteria ( Ventosa et al, 1998 ), and members of this genus have also been found in non-marine systems such as Salar de Atacama, where the relation between pigmentation and salt tolerance was investigated ( Gallardo et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, our small sample size prevented us from determining if this pattern is consistent across species or if some bacterial taxa show a stronger contribution to microbiome diversity than others. Microbiome composition could also be influenced by habitat type [65][66][67][68][69][70], particularly because we sampled one fresh and two brackish-water sites. Indeed, we found significant differences in the number of ASVs across sites, with brackish-water sites showing the highest number of unique bacterial taxa.…”
Section: Bacterial Diversity and Core Microbiome Of Water Stridersmentioning
confidence: 99%
“…Due to the diversity among prodiginine-producing bacteria, it is difficult to determine the precise biological and ecological role of the pigment. Based on previous studies, it can be inferred that prodiginine may provide a mode of defense against competing microorganisms or a potential response to environmental stressors (Gallardo et al, 2016).…”
Section: Introductionmentioning
confidence: 99%